Total production time minimization of a multi-pass milling process via cuckoo optimization algorithm. Issue 1 (October 2016) - Mellal, Mohamed; Williams, Edward
Abstract The milling process is a widely used conventional machining operation. Due to economic reasons, the multi-pass milling process is more convenient. However, the required time for machining increases and an optimization solution must be undertaken. In this paper, the total production time is minimized by resorting to a powerful bio-inspired algorithm, called the cuckoo optimization algorithm. The constraints are successfully handled and the optimal results are compared with those available in the literature. It is shown that the present results are better.